2019
DOI: 10.1083/jcb.201809121
|View full text |Cite|
|
Sign up to set email alerts
|

Yorkie controls tube length and apical barrier integrity during airway development

Abstract: Epithelial organ size and shape depend on cell shape changes, cell–matrix communication, and apical membrane growth. The Drosophila melanogaster embryonic tracheal network is an excellent model to study these processes. Here, we show that the transcriptional coactivator of the Hippo pathway, Yorkie (YAP/TAZ in vertebrates), plays distinct roles in the developing Drosophila airways. Yorkie exerts a cytoplasmic function by binding Drosophila Twinstar, the orthologue of the vertebrate actin-severing protein Cofil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 84 publications
(120 reference statements)
0
15
0
Order By: Relevance
“…Multiple aECM regulators are repressed by Blimp-1 25 , whose activity may be regulated by the feedback mechanism that regulates taenidial spacing 53 . The Hippo pathway transcription factor Yorkie (YAP/TAZ) has a dual role in tracheal morphogenesis, promoting tube elongation via the expression of cytoskeletal factors, and promoting water tightness via expression of the crosslinking enzyme Alas 26 . YAP/TAZ signaling may coordinate the regulation of tracheal cytoskeletal dynamics and the aECM.…”
Section: Tracheal Tube Morphogenesis and The D Melanogastementioning
confidence: 99%
“…Multiple aECM regulators are repressed by Blimp-1 25 , whose activity may be regulated by the feedback mechanism that regulates taenidial spacing 53 . The Hippo pathway transcription factor Yorkie (YAP/TAZ) has a dual role in tracheal morphogenesis, promoting tube elongation via the expression of cytoskeletal factors, and promoting water tightness via expression of the crosslinking enzyme Alas 26 . YAP/TAZ signaling may coordinate the regulation of tracheal cytoskeletal dynamics and the aECM.…”
Section: Tracheal Tube Morphogenesis and The D Melanogastementioning
confidence: 99%
“…Recently, work from Skouloudaki et al, Xu et al, and Meyer et al showed that Yki in the Drosophila trachea/wing disc and YAP in murine hepatocytes are enriched in the apical F-actin area, where they interact with actin cytoskeleton molecules to regulate tissue morphogenesis [ 14 , 18 , 19 ]. More specifically, these groups found that Yki and YAP interact with actin cytoskeletal components, such as Twinstar (Tsr), Trio, Dia, and Cingulin.…”
Section: Apical Cell Cortex: a Site Of Yap/yki And Actin Cytoskelementioning
confidence: 99%
“…More recent data have demonstrated a novel mechanism by which hepatocytes sense organ size during liver regeneration by means of changes in the apical actomyosin network that trigger YAP nuclear translocation [ 14 ]. The relationship of YAP/Yki and actin cytoskeleton is bidirectional, with studies indicating that the Hippo pathway regulates actin cytoskeleton in Drosophila [ 10 , 15 , 16 , 17 , 18 , 19 ]. Moreover, other groups have demonstrated the interaction of core Hippo pathway components, including Yki, with F-actin regulators [ 18 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the dynamic behaviour of Ncaph and Ncaph2 in live haematopoietic precursors, we used Fluorescence Correlation Spectroscopy (FCS). Due to the low incident light intensities used in FCS, it is a reasonably non-invasive method with single molecule sensitivity that allows the dynamic behaviour of fluorescent molecules (e.g., their molecular movement / diffusion) to be analysed in living cells at physiological concentrations [39][40][41][42][43][44] . In FCS, fluctuations in fluorescence intensity are recorded at high temporal resolution, and then used to infer the molecular movement of molecules entering or leaving a subfemtoliter detection volume ( Figure 4A).…”
Section: Distinct Condensin Dynamics In Live Haematopoietic Cellsmentioning
confidence: 99%